Tears evoke the intention to offer social support: A systematic investigation of the interpersonal effects of emotional crying across 41 countries - H.Zickfeld Janis; de Ven Nielsvan; Pich Olivia; W.Schubert Thomas; B.Berkessel Jana; J.Pizarro José; Bhushan Braj; Mateo Nino Jose; Barbosa Sergio; Sharman Leah; Kökönyei Gyöngyi; Schrover Elke; et al. (Elsevier, 2022)
Tearful crying is a ubiquitous and likely uniquely human phenomenon. Scholars have argued that emotional tears serve an attachment function: Tears are thought to act as a social glue by evoking social support intentions. Initial experimental studies supported this proposition across several methodologies, but these were conducted almost exclusively on participants from North America and Europe, resulting in limited generalizability. This project examined the tears-social support intentions effect and possible mediating and moderating variables in a fully pre-registered study across 7007 participants (24,886 ratings) and 41 countries spanning all populated continents. Participants were presented with four pictures out of 100 possible targets with or without digitally-added tears. We confirmed the main prediction that seeing a tearful individual elicits the intention to support, d = 0.49 [0.43, 0.55]. Our data suggest that this effect could be mediated by perceiving the crying target as warmer and more helpless, feeling more connected, as well as feeling more empathic concern for the crier, but not by an increase in personal distress of the observer. The effect was moderated by the situational valence, identifying the target as part of one's group, and trait empathic concern. A neutral situation, high trait empathic concern, and low identification increased the effect. We observed high heterogeneity across countries that was, via split-half validation, best explained by country-level GDP per capita and subjective well-being with stronger effects for higher-scoring countries. These findings suggest that tears can function as social glue, providing one possible explanation why emotional crying persists into adulthood.